Preventing Harm or Securing Certainty? Disparities in Religious Court Rulings on Polygamy Permits Resulting from Pregnancy Out of Wedlock - Sifa Mulya Nurani; Oyo Sunaryo Mukhlas; Siah Khosyi'ah; Ramdani Wahyu Sururie; Rohmad Nurhuda (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2026)
The pregnancy of a prospective second wife outside of marriage is not explicitly regulated by law as a valid reason for permitting polygamy, thus creating a legal vacuum and disparities in rulings by religious courts. This study aimed to investigate the causes of these disparities by comparing the Karangasem Religious Court (PA) Decision No. 1/Pdt. G/2018/PA.Kras, which granted the petition, and the Kaimana Religious Court (PA) Decision No. 22/Pdt. G/2019/PA.Kmn, which rejected it. This qualitative study employed a juridical-normative approach. Data collection was conducted through a document analysis of primary legal materials—namely, the two rulings—which were then analyzed using content analysis through the lens of Satjipto Rahardjo’s Progressive Law. The results of the study revealed a sharp divergence in the judges’ legal reasoning. The Karangasem Religious Court judge demonstrated a non-positivist and contextual approach that prioritizes substantive justice by boldly making legal innovations to protect children. The judge applied the fiqh principle of dar’ul mafasid muqaddamun ‘ala jalbil mashalih (preventing harm takes precedence over seeking benefit). In contrast, the judge at the Kaimana Religious Court adopted a rigid, positivistic, and textual approach, strictly adhering to the formal requirements of Law No. 1 of 1974, without considering the sociological urgency of the pregnancy. This study concludes that a progressive legal perspective is highly relevant to this specific case, in which the law serves to protect human beings and prevent greater harm to the legal status of mothers and children.